Rhizobium meliloti genes required for nodule development are related to chromosomal virulence genes in Agrobacterium tumefaciens - Dylan, T. (1986)
Symbiotically essential genes have been identified in Rhizobium meliloti that are structurally and functionally related to chromosomal virulence (chv) genes of Agrobacterium tumefaciens. Homologous sequences also exist in the genomes of other fast-growing rhizobia including Rhizobium trifolii, Rhizobium leguminosarum, and Rhizobium phaseoli. In Agrobacterium, the chvA and chvB loci are known to be essential for oncogenic transformation of dicotyledonous plants and for attachment to plant cells [Douglas, C. J., Staneloni, R. J., Rubin, R. A. & Nester, E. W. (1985) J. Bacteriol. 64, 102-106], and the chvB locus has been implicated in the production of (1→2)-β-glucan, a unique exopolysaccharide component [Puvanesarajah, V., Schell, F. M., Stacey, G., Douglas, C. J. & Nester, E. W. (1985) J. Bacteriol. 164, 102-106]. Site-directed transposon insertion mutants in the chvA and chvB-equivalent regions of R. meliloti are symbiotically defective. Mutants in the chvB-equivalent region have been examined in detail and have been found to induce the formation of nodule-like structures on alfalfa that are devoid of bacteroids, lack infection threads, and cannot fix nitrogen. Such mutants fluoresce normally in the presence of Calcofluor, a histochemical stain for β-linked polysaccharides, and produce normal amounts of total exopolysaccharide. The Rhizobium loci have been designated ndv because of their requirement for nodule development.